Assessing the species diversity in non-conservation areas: A first systematically camera trapping survey in Batang Angkola Landscape, North Sumatra, Indonesia - Anton Ario; Sarmaidah Damanik; Ahsan Rabbani; Berto Dionisius Naibaho; Abdul Rojak Hasibuan; Sahiruddin Hasibuan; Muhammad Arif Hasibuan; Ambet Harianja (Universitas Pakuan, 2020)
Assessing the species diversity in non-conservation areas is crucial to understanding for conservation interventions and management. We used camera trapping to investigate the species diversity in the Batang Angkola Landscape in North Sumatra. The study on species diversity in the area was conducted in 5 months from February to June 2020. The aim of this study is to assess the species diversity in Batang Angkola landscape as a reference for the improvement of the management and policy with a special interest in proving the existence of wildlife species in the landscape. We compiled a species diversity, richness and evenness investigated conducted a test to Shannon wiener analyses. Based on 1,283 photograph at 60 camera traps stations during 2,923 trap days, we identified 27 different species (24 species are terrestrial mammals, 2 species are birds, and 1 species is reptile), including five classified as threatened according to the IUCN. Based on the calculation of the Relative Abundance Indices for each species per 100 trap days, pig-tailed macaque had the highest RAI (3.63 photograph /100 trap days), followed by wild boar and muntjac were (1.33 and 1.27 photographed/100 traps days respectively). Based on Shannon Weiner analysis shows the analysis of species diversity (H), which showed that in the northern and southern areas it was moderate (2.40 and 2.45 respectively). The level of evenness between north and south areas shows high evenness (0.77 and 0.79 respectively). The level of species richness between north and south shows moderate to high levels in the two areas (3.95 and 4.42 respectively). Our findings suggest that Batang Angkola Landscape supports a high species richness. Continued survey efforts need to be combined with detailed ecological data collection and effective management in the region.Menilai keanekaragaman spesies di kawasan non-konservasi sangat penting untuk memahami upaya pengelolaan dan intervensi konservasi. Kami menggunakan camera trap untuk menyelidiki keanekaragaman spesies di Bentang Alam Batang Angkola di Sumatera Utara. Kajian keanekaragaman jenis di kawasan ini dilakukan selama 5 bulan dari Februari hingga Juni 2020. Tujuan penelitian ini adalah untuk mengkaji keanekaragaman jenis di bentang alam Batang Angkola sebagai acuan perbaikan tata kelola dan kebijakan, spesifik pada membuktikan keberadaan spesies satwa liar. Data keanekaragaman spesies, kekayaan dan kemerataan yang kami kumpulkan, dianalisis dengan Shannon wiener. Berdasarkan 1.283 foto di 60 stasiun perangkap kamera selama 2.923 hari rekam, kami mengidentifikasi 27 spesies berbeda (24 spesies mamalia darat, 2 spesies burung, dan 1 spesies reptil), termasuk lima jenis yang diklasifikasikan sebagai satwa terancam menurut IUCN. Berdasarkan perhitungan Indeks Kelimpahan Relatif untuk setiap spesies per 100 hari rekam, beruk memiliki RAI tertinggi (3,63 foto / 100 hari rekam), disusul babi hutan dan kijang (masing-masing 1,33 dan 1,27 foto / 100 hari rekam). Berdasarkan analisis Shannon-Weiner untuk keanekaragaman jenis (H) menunjukkan bahwa di wilayah utara dan selatan dalam kategori sedang (masing-masing 2,40 dan 2,45). Tingkat kemerataan antara wilayah utara dan selatan menunjukkan tingkat kategori kemerataan yang tinggi (masing-masing 0,77 dan 0,79). Tingkat kekayaan spesies antara utara dan selatan menunjukkan kategori tingkat sedang hingga tinggi di kedua wilayah tersebut (masing-masing 3,95 dan 4,42). Temuan kami menunjukkan bahwa Bentang Alam Batang Angkola mendukung kekayaan spesies yang tinggi. Upaya survey lanjutan perlu digabungkan dengan pengumpulan data ekologi yang terperinci dan pengelolaan yang efektif di wilayah tersebut.